Products From Olive Tree 2016
DOI: 10.5772/64494
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Based Approaches for Traceability and Authentication of Olive Oil

Abstract: Abstract"uthentication and traceability of extra virgin olive oil is a challenging research task due to the complexity of fraudulent practices. Various chemical and biochemical techniques have been developed for determining the authenticity of olive oil and in recent years non-conventional methods based on DN" analysis have gained atention, due to high speciicity, sensitivity and reliability. DN" analyses have very high discriminating power because ultimately the unique identity of a variety or species is to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…However, they present some limits due to the difficulty in identifying the olive varieties used for oil production. Instead, DNA-based methods are more accurate and reliable than chemical methods; moreover, they are not influenced by environmental conditions [13]. Among the genetic markers used for cultivar identification and varietal traceability in processed foods, simple sequence repeats (SSRs) and single nucleotide polymorphisms (SNPs) are the most suitable [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, they present some limits due to the difficulty in identifying the olive varieties used for oil production. Instead, DNA-based methods are more accurate and reliable than chemical methods; moreover, they are not influenced by environmental conditions [13]. Among the genetic markers used for cultivar identification and varietal traceability in processed foods, simple sequence repeats (SSRs) and single nucleotide polymorphisms (SNPs) are the most suitable [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by identifying the number of repeats found in the DNA isolated from a sample, a process performed by amplifying the target sequence by PCR amplification using specific primers, discrimination of the variety can be achieved. Usually, a combination of SSR markers is used to provide a more powerful discriminatory analysis (Bazakos et al, 2016). Some applications include expressed sequence tag SSR (EST-SSR), which derive from regions of the genome that are expressed (sequence coding for a specific protein) and therefore these regions have greater transferability among species and their variation can be associated with the phenotype (Duran et al, 2009).…”
Section: Simple Sequence Repeats (Ssr)mentioning
confidence: 99%
“…RAPD, AFLP and ISSR have advantages when analyzing genetic relationships in olive trees mainly because the design of primers for the PCR do not require prior knowledge of the genome sequence. However, these markers have the drawback of low reproducibility in olive oil studies (reviewed by Pasqualone et al, 2016;Sebastiani and Busconi, 2017;Bazakos et al, 2016, Ben-Ayed et al, 2013. The genetic markers used by the most recent studies for olive oil authentication are simple sequence repeats (SSR) and single nucleotide polymorphisms (SNPs) (Pasqualone et al, 2016) and are located either in nuclear DNA or in the DNA found in organelles (chloroplast or mitochondrial DNA) (Pereira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%